Kewenangan Pemungutan Pajak Rokok Dalam Kaitannya Dengan Jaminan Kesehatan Nasional - Kristophorus Gerin Novendra (Faculty of Law, Universitas Airlangga, 2022)
AbstractCigarette Tax is included in local taxes, to be precise it is a provincial taxes. But in Statute Number 28 of 2009 concerning Regional Taxes dan Regional Levies, Cigarette Tax are collected by the central government institute authorized to collect excise. In that Regulation its is also explained that provincial taxes is the full authority of provincial government so based on that ther is a conflict of norms on the authority to collect cigarette taxes. Cigarette tax as a provincial tax which is also a source of regional income based on the Minister of Finance Regulation Number 128/PMK.07/2018 concerning the Procedure for Withholding Cigarette Tax as a Contribution to Support for the Health Assurance Program must be deducted by 50% to finance the National Health Assurance program so that it affects on regional development.Keywords: Cigarette Tax; Authority; National Health Assurance. AbstrakPajak rokok termasuk dalam pajak daerah, tepatnya pajak daerah provinsi. Dalam Undang-Undang Nomor 28 Tahun 2009 tentang Pajak Daerah dan Retribusi Daerah, Pajak Rokok dipungut oleh instansi pemerintah pusat yang berwenang memungut cukai. Dalam Undang-undang tersebut dijelaskan juga bahwa pajak daerah merupakan kewenangan penuh pemerintah daerah sehingga terdapat konflik norma atas kewenangan pemungutan pajak rokok. Pajak rokok sebagai pajak daerah yang juga merupakan sumber pendapatan daerah berdasarkan Peraturan Menteri Keuangan Nomor 128/PMK.07/2018 tentang Tata Cara Pemotongan Pajak Rokok sebagai Kontribusi Dukungan Program Jaminan Kesehatan harus dipotong sebesar 50% untuk pembiayaan program Jaminan Kesehatan Nasional sehingga berdampak pada pembangunan daerah. Kata Kunci: Pajak Rokok; Kewenangan; Jaminan Kesehatan Nasional.